Hiccups Following Dexamethasone- Cyclophosphamide Pulse Therapy In a Patient With Oral Pemphigoid - Pai Sathish; Srinivas C R; Shenol S D (Wolters Kluwer Medknow Publications, 1997)
Dexamethasone â€" cyclophosphamide pulse therapy is effective in the treatment of bullous and connective tissue disorders. Hiccups following pulse therapy is reported.